The Fox went out on a chilly night : an old song - Spier, Peter, 1927-2017 (New York : Doubleday, 1989)
The countryside of New England is depicted in the pictures accompanying this folk song in which a fox travels many miles to get dinner for his wife and ten cubs.
"Caldecott Honor Book"--Seal on Cover.
Keywords: Children's songs, English -- United States -- Texts; Folk songs, English -- United States -- Texts; English songs; Folk songs -- England; Foxes; Song texts